Hackers, hot rods, and the information drag strip. - Whitehorn-Umphres, D. (IEEE spectrum)
Over the last decade, automobiles have become increasingly digital. High-end vehicles have dozens of microcontrollers (MCs), and even the simplest ?econoboxes? have as many as 10. These MCs range from the simplest measurement and response systems to general-purpose central processing units. More importantly, all of the sensors, actuators, and MCs are hooked into one of three styles of networks, as defined by the Society of Automotive Engineers: Class A: low speed (less than 10 kb/s), used for convenience features; Class B: medium speed (10-125 kb/s), used for general information transfer (emissions data, instrument cluster, speed); and Class C: high speed (more than 125 kb/s), real-time control (powertrain, brake-by-wire, active suspension). In other words, the faster the network, the more important and safety critical it becomes. The discusses the hacking aspect of this digital technology and how it could be enhanced or altered to get round safety features or make on-the-road modifications that much easier. What the car manufacturers and their engineers do not realize is that the convergence of automotive engineering and digital technologies is already enabling the next generation of hot rodding. Physical hot rodding isn't cheap because it often involves the inadvertent testing to destruction of new ideas and components. Digital hot rodding, though, where software is used to modify how a vehicle does something, is orders of magnitude cheaper and far more accessible